Pengaruh Brand Image, Lifestyle Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Iphone Di Kota Mataram - mawati, War; Retnowati, Weni; minah, Rus (Journal of Sharia Economy and Islamic Tourism, 2022)
This study aims to examine the effect of brand image, lifestyle, and product quality on iPhone smartphone purchasing decisions in Mataram City. So that this research variable consists of 3 (three) independent variables, namely brand image (X1), lifestyle (X2), and product quality (X3) and 1 (one) dependent variable, namely purchasing decisions (Y). The population in this study are all consumers who live or are domiciled in the Mataram City area who have purchased an iPhone Smartphone. Respondents in this study amounted to 100 respondents.The results of this study indicate that the brand image (X1) and lifestyle (X2) variables have a positive but not significant effect on the iPhone smartphone purchase decision. This is evidenced by the results of the t-test of the brand image variable (X1) which is the t-count value of 0.232 where this value is smaller than the t-table of 1.985. The t test criteria if sig (0.817) > 0.05 then the brand image variable has no significant effect on the iPhone smartphone purchase decision, and the t test results on the lifestyle variable (X2) is the t count value of 0.781 where this value is smaller than the t table of 1,985. The t test criteria if sig (0.437) > 0.05 then the lifestyle variable has no significant effect on the iPhone smartphone purchase decision. While the results of the product quality variable (X3) have a positive and significant effect on the iPhone smartphone purchase decision. This is evidenced by the results of the t-test, namely that the t-count value is 7.091 where this value is greater than the t-table of 1.985. The t-test criteria if sig (0.000) <0.05 then the product quality variable has a positive and significant effect on the iPhone smartphone purchase decision.ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh brand image, lifestyle, dan kualitas produk terhadap keputusan pembelian smartphone iPhone di Kota Mataram. Sehingga variabel penelitian ini terdiri dari 3 (tiga) variabel independen yaitu brand image (X1), lifestyle (X2), dan kualitas produk (X3) serta 1 (satu) variable dependen yaitu keputusan pembelian (Y). populasi dalam penelitian ini adalah seluruh konsumen yang bertempat tinggal atau berdomisili di wilayah Kota Mataram yang pernah melakukan pembelian Smartphone iPhone. Responden dalam penelitian ini berjumlah 100 responden.Hasil pada penelitian ini menunjukkan bahwa variabel brand image (X1) dan lifestyle (X2) berpengaruh positif namun tidak signifikan terhadap keputusan pembelian smartphone iPhone. Hal ini dibuktikan dengan hasil uji t dari variabel brand image (X1) adalah nilai t hitung sebesar 0,232 dimana nilai ini lebih kecil dari t tabel sebesar 1,985. Kriteria uji t jika sig (0,817) >0,05 maka variabel brand image tidak berpengaruh signifikan terhadap keputusan pembelian smartphone iPhone, dan dan hasil uji t pada variabel lifestyle (X2) adalah nilai t hitung sebesar 0,781 dimana nilai ini lebih kecil dari t tabel sebesar 1,985. Kriteria uji t jika sig (0,437) >0,05 maka variabel lifestyle tidak berpengaruh signifikan terhadap keputusan pembelian smartphone iPhone. Sedangkan hasil dari variabel kualitas produk (X3) berpengaruh positif dan signifikan terhadap keputusam pembelian smartphone iPhone. Hal ini dibuktikan dengan hasil uji t yaitu bahwa nilai t hitung sebesar 7,091 dimana nilai ini lebih besar dari t tabel sebesar 1,985. Kriteria uji t jika sig (0,000) <0,05 maka variabel kualitas produk berpengaruh positif dan signifikan terhadap keputusan pembelian smartphone iPhone.